2018
DOI: 10.1186/s40360-018-0217-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the state of pharmacovigilance in the South-South zone of Nigeria using WHO pharmacovigilance indicators

Abstract: BackgroundWHO pharmacovigilance indicators have been recommended as a useful tool towards improving pharmacovigilance activities. Nigeria with a myriad of medicines related issues is encouraging the growth of pharmacovigilance at peripheral centres. This study evaluated the status of pharmacovigilance in tertiary hospitals in the South-South zone of Nigeria with a view towards improving the pharmacovigilance system in the zone.MethodsA cross-sectional descriptive survey was conducted in six randomly selected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 23 publications
2
30
0
Order By: Relevance
“…As stated by other hospital-based HTA experiences (2;3;12), we also learned during these years that political will and leadership support are the prime success factors for the establishment and implementation of an HTA. At the KHCC, the higher administration and the pharmacy department administration supported the initiation and the development of HTA.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…As stated by other hospital-based HTA experiences (2;3;12), we also learned during these years that political will and leadership support are the prime success factors for the establishment and implementation of an HTA. At the KHCC, the higher administration and the pharmacy department administration supported the initiation and the development of HTA.…”
Section: Discussionmentioning
confidence: 71%
“…Our results showed that our HTA program is functional and effective. As stated by the best practices of hospital-based HTA and key principles for conducting HTA (2;3;12), the minimum core requirements for a hospital-based HTA program are available. The KHCC has embedded HTA activities within the organizational structure of the KHCC, which makes it more structured than hospital-based activities in other countries (24;3032).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…17,18 Evaluating a pharmacovigilance system will facilitate actions to remedy the identified deficiencies to improve ADR reports' quantity and quality, leading to more rigorous decision-making in pharmacovigilance. 19 Currently, the assessment of pharmacovigilance has mainly been carried out at the national level using different tools, including the WHO Minimum Requirements for a Functional Pharmacovigilance System, 5 and the Indicator based Pharmacovigilance Assessment Tool. 20 WHO pharmacovigilance indicators were introduced in 2015.…”
Section: Introductionmentioning
confidence: 99%